Low doses of the NMDA receptor antagonists, MK-801, PEAQX, and ifenprodil, induces social facilitation in adolescent male rats - Morales, Melissa (2013)
Adolescents display high levels of interactions with peers relative to other age groups, with these interactions further enhanced by ethanol under some circumstances. Understanding of the neural mechanisms underlying these high levels of social interactions is important given that alcohol use is initiated during adolescence and adolescents tend to report drinking for social reasons. Given that ethanol’s effects are associated in part with functional antagonism of the NMDA receptor system, the current experiment explored the role of NMDA antagonists for facilitating adolescent social behavior. Adolescent male Sprague-Dawley rats were challenged acutely with either the non-competitive NMDA antagonist, MK-801 (0.01, 0.03 mg/kg), the NR2A antagonist, PEAQX (1.25, 3.75 mg/kg) or the NR2B antagonist, ifenprodil (0.75, 2.25 mg/kg) 30 min prior to a 10-min social interaction test. All compounds generally increased overall social activity (i.e., sum of social investigation, contact behavior, and play), with ifenprodil also significantly enhancing play and social contact behaviors. Although the frequencies of peer-directed social behaviors were typically greater following administration with these NMDA antagonists, social preference, indexed via the number of crossovers to the side with the partner relative to crossovers away, was significantly reduced in MK-801 and PEAQX-treated rats. None of these changes were associated with concomitant alterations in overall locomotor activity under these test circumstances. These data support the suggestion that the increases in social interactions observed in adolescents following acute ethanol may be driven in part by NMDA receptor antagonism—particularly of the NR2B subunit—given that ifenprodil stimulated social behavior in a manner similar to that produced by low doses of ethanol.